A Study on Urban Renewal Strategies of Shuozhou City, Shanxi Province, China Based on Stakeholder Theory and Social Network Analysis - Xiaoting Ma; Nangkula Utaberta; Nadzirah Zainordin (Future Cities and Environment, 2023)
China has undergone an unprecedented period of rapid urbanization in recent decades, resulting in a host of urban challenges. In response to these issues, urban renewal has emerged as a proactive policy approach to address urban problems. Urban regeneration is a multifaceted and multi-level endeavor that involves numerous stakeholders. Investigating the formulation of urban regeneration strategies in light of these stakeholders is pivotal for resolving societal issues and enhancing the comprehensiveness and feasibility of urban regeneration strategies.This paper employs Shuozhou City as a case study, using a combination of stakeholder theory and social network analysis to identify stakeholders in the context of urban renewal. It conducts a comprehensive stakeholder analysis, explores the social network structure among these stakeholders, and constructs an “impact-interest” matrix to capture their roles and interests. Based on this matrix, it proceeds to propose a range of dimension-specific urban renewal strategies for Shuozhou City.In conclusion, leveraging this matrix, the paper outlines specific strategies tailored to the urban renewal context in Shuozhou, exemplifying the potential for a more effective approach to addressing urban challenges.